Building a safer foundation: the Lessons Learnt patient safety training programme. - Ahmed, M; Arora, S; Tiew, S; Hayden, J; Sevdalis, N; Vincent, C; Baker, P (2014)
OBJECTIVES: To develop, implement and evaluate a novel patient safety training programme for junior doctors across a Foundation School-'Lessons Learnt: Building a Safer Foundation'. DESIGN, SETTING AND PARTICIPANTS: Prospective preintervention /postintervention study across 16 Foundation Programmes in North West England, UK. 1169 participants including all Foundation Programme Directors, Administrators, Foundation trainees and senior faculty. INTERVENTIONS: Half-day stakeholder engagement event and faculty development through recruitment and training of local senior doctors. Foundation trainee-led monthly 60-min sessions integrated into compulsory Foundation teaching from January to July 2011 comprising case-based discussion and analysis of patient safety incidents encountered in practice, facilitated by trained faculty. MAIN OUTCOME MEASURES: Participants' satisfaction and Foundation trainees' patient safety knowledge, skills, attitudes and behavioural change. RESULTS: Participants reported high levels of satisfaction with 'Lessons Learnt'. There was a significant improvement in trainees' objective patient safety knowledge scores (Meanpreintervention=51.1%, SD=17.3%; Meanpostintervention=57.6%, SD=20.1%, p<0.001); subjective knowledge ratings and patient safety skills. Trainees' perceived control and behavioural intentions regarding safety improved significantly postintervention. Feelings and personal beliefs about safety did not shift significantly. Trainees reported significantly more patient safety incidents in the 6 months following introduction of 'Lessons Learnt' (Meanpreintervention=0.67, SD=1.11; Meanpostintervention=1.18, SD=1.46, p<0.001). 32 quality improvement projects were initiated by trainees, spanning the development of novel clinical protocols; implementation of user-informed teaching and improved rota design CONCLUSIONS: Patient safety training can be implemented and sustained to deliver significant improvements in patient safety knowledge, skills and behaviours of junior doctors-with potential for wider positive organisational impact. Medical education commissioners and providers could adopt and build upon the 'Lessons Learnt' approach as a springboard to promote medical engagement in quality and safety improvement.